Aging Patient Population With Ruptured Aneurysms: Trend Over 28 Years. Issue 3 (28th March 2021) - Feghali, James; Gami, Abhishek; Rapaport, Sarah; Bender, Matthew T; Jackson, Christopher M; Caplan, Justin M; McDougall, Cameron G; Huang, Judy; Tamargo, Rafael J
Abstract: BACKGROUND: Given increasing life expectancy in the United States and worldwide, the proportion of elderly patients affected by aneurysmal subarachnoid hemorrhage (aSAH) would be expected to increase. OBJECTIVE: To determine whether an aging trend exists in the population of aSAH patients presenting to our institution over a 28-yr period. METHODS: A prospectively maintained database of consecutive patients presenting to our institution with subarachnoid hemorrhage between January 1991 and December 2018 was utilized. The 28-yr period was categorized into 4 successive 7-yr quarter intervals. The age of patients was compared among these intervals, and yearly trends were derived using linear regression. RESULTS: The cohort consisted of 1671 ruptured aneurysm patients with a mean age of 52.8 yr (standard deviation = 15.0 yr). Over the progressive 7-yr time intervals during the 28-yr period, there was an approximately 4-fold increase in the proportion of patients aged 80 yr or above ( P  < .001) and an increase in mean patient age from 51.2 to 54.6 yr ( P  = .002). Independent of this trend but along the same lines, there was a 29% decrease in the proportion of younger patients (<50 yr) from 49% to 35%. On linear regression, there was 1-yr increase in mean patient age per 5 calendar years ( P  < .001). CONCLUSION: Analyses of aSAH patients demonstrate an increase in patient age over time with a considerable rise in the proportion of octogenarian patients and a decrease in patients younger than 50 yr. This aging phenomenon presents a challenge to the continued improvement in outcomes of aSAH patients.